SYMBOLS USED IN “LARUNGAN” AT NGEBEL LAKE PONOROGO REGENCY - Widastuti, Rini; Wuryantoro, Aris (Prosiding PESAT, 2015)
This research is intended to reveal about symbols used in Larungan at Ngebel lake, Ponorogo Regency, East Java, Indonesia. The objectives of the research are: (1) describing the kinds of symbols used in Larungan at Ngebel lake, and (2) analyzing the meaning of symbols used in Larungan at Ngebel lake. The research uses descriptive qualitative research by using semiotic approach. Data of the research collected by using observation, interview, and content analysis from the informant and documentation. Results of the research reveal that: (1) there are thirteen symbols used in Larungan at Ngebel lake, Ponorogo, as follows Wedus Kendit (Stripped stomach goat), Tumpeng Abang (Red coned rice), Buceng Kuwat (Forcing coned white sticky rice). Buceng Tulak (Warding coned white sticky rice), Jenang (Rice pudding), Rasulan (attribute to Muhammad, the messenger of God), Leluwuran (Prayer for ancestors), Pala Pendem, Kupat lan Kupat Lepet (Buried corps plant, Rice boiled of plaited young coconut leaves, and Sticky rice of twisted young coconut leaves), Sego Golong Limo lan Sego Golong Pitu (Five piled rice and seven piled rice), Beras Sefitrah, Kambil Gundil, Pisang Ayu (One tithe rice, one skinless coconut, and good condition of banana), Kupat Luwar (Kind of rice boiled of plaited young coconut leaves), Gulo Gimbal Karuk Gringsing (Sticky sugar with fried dried rice), Tumpeng Agung (Big coned rice); and (2) every symbol used in the Larungan has each meaning depend on its purposes. It concludes that symbols used in Larungan contain some meaning which reflected in the form of foods. Every symbol has the relationship with macrocosm meaning that is the relationship between the Ngebel villagers and the God, and microcosm meaning has relationship with the process of Larungan itself.